A variational eigenvalue solver on a photonic quantum processor. - Peruzzo, Alberto.; McClean, Jarrod.; Shadbolt, Peter.; Yung, Man-Hong.; Zhou, Xiao-Qi.; Love, Peter J.; Aspuru-Guzik, Alán.; O'Brien, Jeremy L. (Tufts University. Tisch Library., 2018)
Quantum computers promise to efficiently solve important problems that are intractable on a conventional computer. For quantum systems, where the physical dimension grows exponentially, finding the eigenvalues of certain operators is one such intractable problem and remains a fundamental challenge. The quantum phase estimation algorithm efficiently finds the eigenvalue of a given eigenvector but requires fully coherent evolution. Here we present an alternative approach that greatly reduces the requirements for coherent evolution and combine this method with a new approach to state preparation based on ansätze and classical optimization. We implement the algorithm by combining a highly reconfigurable photonic quantum processor with a conventional computer. We experimentally demonstrate the feasibility of this approach with an example from quantum chemistry - calculating the ground-state molecular energy for He-H+. The proposed approach drastically reduces the coherence time requirements, enhancing the potential of quantum resources available today and in the near future. © 2014 Macmillan Publishers Limited. All rights reserved.